Cationização da celulose microcristalina e utilização como floculante para o tratamento de água - Grade, Bruna Thais Lauer (2022)
All water intended for human consumption must meet pre-established potability standards, and must be free from any impurity or pathogenic organism. In view of this, to guarantee the required potability standards, it is often necessary to carry out a series of treatment steps. Usually, to perform water treatment, chemicals are used, such as aluminum sulfate and ferric chloride, however, the residuals of these elements are related to neurodegenerative diseases, as well as implying damage to the environment. In view of this, an alternative is the use of organic cationic polymers to replace the chemical products used. Cellulose is one of the most important natural polymers, being the most abundant polysaccharide in nature. However, to use it as a cationic polyelectrolyte it is necessary to make changes in its structure. One of the most used reagents for the production of cellulose cations is 3-chloro-2- hydroxypropyltrimethylammonium chloride (CHPTAC). In view of this, the present work sought the production of a cationic polyelectrolyte derived from cellulose, through the cationization process, through the use of the CHPTAC reagent, and its application in the treatment of water, in different pH ranges. The treatment system was simulated using the Jartest equipment, followed by filtration with filter paper. With the study it was concluded that the cationization of cellulose resulted in a degree of substitution of 0.02. And its use as a flocculant resulted in removals of up to 99% for turbidity and 99.6% for color, at pH 3, and a flocculant dosage of 100 mg/L. In the other pH ranges tested (4, 5, 6, 7 and 8) the removals ranged from 66.2 to 97% for color and 88.6 to 97.3% for turbidity, respectively. Thus, the use of cellulosic derivatives are promising alternatives to replace the inorganic coagulants usually used.